No Reference Without Referents - Garcia Ramírez, Eduardo (Revista de Filosofía, 2016)
Sainsbury 2005 and 2009 offers a theory of empty names that purports to account for the content and truth-value of all utterances involving them. The goal is to do this while offering a homogenous semantic treatment: both empty and nonempty names make the same kind of contribution to truth-values. The account is based on a new theory of reference that purports to be an alternative among nondescriptivist accounts. According to the new theory, there is reference even without referents. In this paper I argue that the theory does not offer a homogeneous semantics for names and that, thus, it fails to offer a more satisfactory alternative to the theories already available. I conclude by briefly describing a way in which a theory could in fact offer such homogeneous semantics for names via a cognitive theory of empty names.